Cumulative effects of therapies on disability in relapsing multiple sclerosis. (October 2021) - Rollot, Fabien; Casey, Romain; Leray, Emmanuelle; Debouverie, Marc; Edan, Gilles; Wiertlewski, Sandrine; Vukusic, Sandra; Laplaud, David-Axel
Background: Long-term effectiveness of treatment remains a key question in multiple sclerosis (MS) and the cumulative effects of past treatment have not been investigated so far. Objective: Explore the relationship between treatment exposure and disability risk in patients with relapsing-remitting multiple sclerosis (RRMS). Methods: A total of 2285 adult patients from the French nationwide cohort were included. Outcomes were irreversible EDSS4, and conversion to secondary progression of multiple sclerosis (SPMS). Associations between treatments and risk of disability were assessed using a novel weighted cumulative exposure model, assuming a 3-year lag to account for reverse causality. This flexible approach accounts for past exposure in a multivariate Cox proportional hazards model by computing a weight function. Results: At baseline, mean ± standard deviation age of patients was 33.4 ± 8.9 years and 75.0% were women. A 15-year continuous treatment starting 20 years ago was associated with a decrease in risk of 26% for irreversible EDSS4, and 34% for SPMS compared to a 5-year treatment starting 10 years ago. The risk of disability decreased with increasing duration of exposure to disease-modifying treatment (DMT). Conclusion: Long-term use of treatments in RRMS has a stronger beneficial cumulative impact than only early uses and delays the occurrence of moderate disability and conversion to SPMS.